Redefining Equality in Marriage Laws: An Analysis of Husband-Wife Relations Through Qira`ah Mubādalah - Abed Majidi; Nurul Kartika Laili; Douglas N. Jaime (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2024)
Husband and wife, as two pairs of lovers, are actually built on a partnership relationship, without dominance between the two. However, the practice of domination and subordination of husbands in the institution of marriage is still fertile, and domestic violence often appears. This gap between idealist-normative and historical-empirical is reflected in marriage regulations in Indonesia, such as Law No. 1 of 1974 and Presidential Instruction No. 1 of 1999 on the Compilation of Islamic Law. In this context, the existence of Qira`ah mub is important to study the reinterpretation of marital relations based on justice, equality, and reciprocity. This research method uses a qualitative approach that relies on literature studies. The results of the study explain that this mublà method is built on 3 basic premises: first, the presence of Islam is directed to men and women, and the texts allude to both. Second, the principle of the relationship between the two is a relationship of cooperation and reciprocity, not a totalitarian and hegemonic relationship. Third, Islamic texts are open to reinterpretation. In relation to the existing marriage law in Indonesia, both the UUP and the Compilation of Islamic Law, which is now still legitimizing the superiority of husbands over women, Qira`ah mublà is a critical offer in studying the provisions of the marriage law that are built on reciprocal relationships or complementary and needy relationships.